Pembibitan Durian Unggul Lokal Palopo - Sukriming Sapareng; Muh. Yusuf Idris; Intisari Intisari; St. Maryam Yasin; Rosnina Rosnina (DEDIKASI, 2019)
The breeders of local superior durian seeds and other superior fruit plant nurseries have been researchedand produced by the Unanda Faculty of Agriculture at the Experimental Gardens and Agro technology Nurseries.The uniqueness of the nursery business is it has low competitors who make superior products based on local durianseed breeders. The annual outputs to be achieved by the PPUPIK Business Unit of Palopo Local Superior SuperiorDurian Seed Breeders were (1) the implementation of the neatly arranged PPUPIK Business Unit Business, (2) theavailability of a good governance system, namely database of superior research and technology, database of clientneeds, and client satisfaction index, (3) availability of PPUPIK unit activity guidelines and the creation of a workingmechanism for PPUPIK units, (4) guaranteed sources of broodstock that is produced by Unanda Palopo, and (5)generated a new entrepreneurship program from the students.